The Development of Sustainable Tourism Destination Area: Spatial Planning in The Tuktuk Siadong Tourist Village, Samosir Regency - Wahyu Hidayat; Muhammad Baiquni; Andri Kurniawan (Department of Geography Education, University of Jember, 2023)
Lake Toba is still surrounded by a stunningly lush environment and one of the biggest lakes in Asia and the world. Gradually, this tourist destination began to be recognized by the people of Indonesia and also the world. The tourist village located in Tuktuk Siadong Village is in an area of the peninsula of Lake Toba, in this tourist village you can find many hotels with various choices and always offer direct views of Lake Toba. This study aimed to describe the spatial development of Tuktuk Siadong Village in Samosir Regency based on tourist destination attributes such as tourist attractions and tourist characteristics. This study used a qualitative descriptive methodology to assess spatial development considering the attributes of popular tourist sites, including tourist attractions and visitor traits. The results showed that the spatial development in the study area was more spread out following the existing circulation path and following the traditional Batak development pattern which produces clusters and is unrelated to the major transportation channel. Tuktuk Siadong Village will become a tourist destination, with cultural tourism attractions from Huta Batak in sight. The landscape, which is a component of the spatial structure, must be preserved along with traditional settlements. The spatial development of the tourism area on Lake Toba can refer to the model that has been prepared so that it can make tourism on Lake Toba in a better and more sustainable direction. Keywords : Sustainable Tourism; Tourism Village; Local Wisdom; Lake Toba Copyright (c) 2023 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License